Tipologi Tafsir Alquran di Indonesia Pasca Reformasi: Telaah Pribumisasi Al-qur’an Karya M. Nur Kholis Setiawan - Husni, Fithriyawan (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2019)
An interpretation is a result of a dialectical process between mufassir, the Qur’anic text, and various factors surrounding it, such as the socio-cultural context, socio-intellectual basis, and the level of spirituality. Indonesia’s socio-political conditions after the Reformation have a different character from the New Order era. There have been political liberation and various social movements, including the Qur’anic interpretation, emerged in this era. This article attempts to analyze a book entitled Pribumisasi Al-Qur’an: Tafsir Berwawasan Keindonesiaan, a representative Qur’anic exegesis which appears in the post-reformation age. The article specifically focuses to examine the typology and methodology initiated by the author. Further, it argues that firstly, the key point of the interpretative thought in Pribumisasi Al-Qur’an lies in the authorship process which is closely related to the author’s social background as santri-academician-bureaucrat. Thus, secondly, the applied method emphasized more on combinative plural thematic interpretation which tends to regard the social nuance with scientific styles and forms of writing.